Occupational first aid in confined spaces or “environments suspected of pollution”: A review of the Italian regulations. - Angelo SACCO (GIornale Italiano di Psicologia e Medicina del Lavoro, 2021)
In Italy, occupational first aid in confined spaces or “environments suspected of pollution” is regulated by Legislative Decree 9 April 2008, no 81 (article 66) and by the Presidential Decree 2011, no 177 (article 3). The Italian confined space safety legislation prohibits the work without putting in place confined spaces safety precautions that are needed to protect workers’ life and physical integrity. These include personal protective equipments, safe system of work, ventilation and emergency procedures. In order to take suitable emergency procedures, the Ministerial Decree 2003 no 388 is not sufficient. Therefore, Italian employers should implement specific emergency measures presented in this review. These include first aid procedures within the emergency plan risk assessment, effective means of communication for raising the alarm both from the confined space and by workers outside, providing rescue and resuscitation equipment on the basis of the likely emergencies identified, ensuring access and a means to safely rescue injured workers. Occupational first aiders should be ready at hand, properly trained, fit to carry out their emergency duties, protected against the cause of the emergency, capable of using any equipment for rescue, including breathing apparatus, lifelines and fire-fighting equipment. Finally, training is critical in all tasks carried out in confined spaces. Training, therefore, should include emergency procedures and specific training in the use of breathing apparatus.